Effect of solvent polarity on the fluorescence properties of )Acriflavine( molecular (Journal of the College of Basic Education, 2022)
The absorption and fluorescence spectra have been studied and measured for Acriflavine (AF) solution which dissolved in [N-N-dimethyl formamide (Dmf) , dimethyl sulphoxide (Dmso) and water] solvents as a function of concentration and solvent at excitation wavelength (λex= 414nm) . Have been calculated peaks the fluorescence spectra of Acriflavine (AF) solution dissolved in N-N-dimethyl formamide (Dmf) and dimethyl sulphoxide (Dmso) at concentration (1x10-5M ) , and found that it is equal to (λmax= 497 ) ، (λmax= 501) and ( λmax= 505), respectively. Also been calculated the value stokes shift of these peaks found to be equal to (1292.5) ، (1316.5) and (2469.7) , respectively. Where we note that (stokes shift) shifted peak of fluorescence spectra towards the longer wavelength (redshift) increases with increase solvent polarity . The increase of solvents polarity lead to decrease in the intensity of the fluorescence spectra . All measurement were at room temperature .